Effects of a 12-Week Hatha Yoga Intervention on Cardiorespiratory Endurance, Muscular Strength and Endurance, and Flexibility in Hong Kong Chinese Adults: A Controlled Clinical Trial. (8th June 2015) - Lau, Caren; Yu, Ruby; Woo, Jean
Abstract : Objective . To examine the effects of a 12-week Hatha yoga intervention on cardiorespiratory endurance, muscular strength and endurance, and flexibility in Chinese adults. Methods . 173 adults (aged 52.0 ± 7.5 years) were assigned to either the yoga intervention group (n = 87 ) or the waitlist control group (n = 86 ). 19 dropped out from the study. Primary outcomes were changes in cardiorespiratory endurance (resting heart rate (HR) and maximal oxygen uptake (V O 2max )), muscular strength and endurance (curl-up and push-up tests), and lower back and hamstring flexibility (the modified back-saver sit-and-reach (MBS) test). Results . Compared to controls, the yoga group achieved significant improvements inV O 2max (P < 0.01 ), curl-up (P < 0.05 ) and push-up (P < 0.001 ) tests, and the MBS left and right leg tests (bothP < 0.001 ) in both genders. Significant change was also found for resting HR between groups in women (P < 0.05 ) but not in men. Further analysis comparing participants between younger and older subgroups yielded similar findings, except that the older participants in the yoga group failed to improve resting HR or the curl-up test versus control. Adherence (89%) and attendance (94%) were high. No serious adverse events occurred. Conclusion . A 12-week Hatha yoga intervention has favorable effects on cardiorespiratory endurance, muscular strength and endurance, and flexibility in Chinese adults.